Use of dance exercises in adaptive physical education for children with intellectual development disabilities - Parfenova, L.A.; Bikmukhametov, R.K. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify scientific approaches and methodological foundations for the use of dance exercises in adaptive physical education for children with intellectual disabilities. Methods and structure of the study. The analysis and synthesis of the scientific positions of classical and modern researchers, structuring, and comparative characteristics allowed us to identify methodological approaches and specific principles of using dance exercises in adaptive physical education of children with intellectual disabilities. Results and conclusions. Theoretical approaches to the use of dance exercises in sports and correctional activities of children with intellectual disabilities have been identified as a methodological basis: neuropsychological (activation and stimulation of functional brain systems through special coordination and rhythmic movements), cultural and historical (dance as a means of development and compensation), activity (dance is a special type of activity, mastering through interiorization), personality-oriented (taking into account individual characteristics), structural-level (hierarchy of motor acts).